The Future of Private Equity in Europe – The Determinants Across Countries - Mihai Precup (Romanian Journal of European Affairs)
This paper examines two aspects related to private equity investments in Europe. First, we will present the evolution of private equity investments across European countries during the last crisis. Second, the paper will analyse and identify the main determinants of the European private equity market, using an empirical panel analysis. The empirical model includes many of the determinants already tested in previous studies (GDP growth, Market Capitalization, Research and Development Expenditures, Interest rates, etc.) and also new variables such as productivity and corruption index which we consider important factors in explaining the evolution of private equity investments in Europe. The present research paper follows the equilibrium model of private equity investments (Gompers and Lerner 1998, Jeng and Wells 2000, Romain and de La Potteria 2004, Félix 2007). We will use aggregated data from European private equity market during 2000–2013, as well as macroeconomic data, in order to estimate a panel data model with fixed and random effects. This paper will also run the Hausman specification test in order to compare the consistency of fixed effects models and random effects models. Our results confirm existent hypotheses regarding the importance of some determinants on the evolution of private equity investments in Europe. However, in the context of the last crisis new factors emerged as important for the private equity market in Europe such as productivity or corruption.